Rancang Bangun Sistem Pengarsipan Surat Masuk dan Surat Keluar (Studi Kasus: Dinas Perhubungan Kota Batam) - Metta Santiputri; Regita Dwi Ayu Lestari (Politeknik Caltex Riau, 2022)
In the process of filing incoming and outgoing letters at the Batam City Transportation Agency, it is still done manually, that is by recording them in a book. All letters are placed in archive folder, then placed in a filing cabinet. With the management of incoming and outgoing letters archives like this can result in accumulating letters archives. Not only that, if you want to find old letter data, it will be difficult to find it. Delivery of incoming letters to certain department is also done manually, that is, delivering the letter to that another department. From these problems, a system regarding letters archiving is built. With this system for filing incoming and outgoing letters, it is hoped that it can help the secretariat department in reducing the difficulty and time spent on delivery and searching for letters data. This system is able to forward incoming letters to any department and archive incoming and outgoing letters. In addition, this system can also print archive reports by the month. The system uses the waterfall method to build. This system also uses the PHP programming language and MySQL as database management system.